Volatile Antimicrobial Agents and In Vitro Methods for Evaluating Their Activity in the Vapour Phase: A Review - Houdkova, Marketa; Kokoska, Ladislav (Planta Medica, 2020)
This review summarizes data on the in vitro antimicrobial effectiveness of volatile agents of plant origin and in vitro methods for evaluating their activity in the vapour phase. As a result of literature analysis, the antimicrobial efficacy of vapours from 122 different plant species and 19 pure compounds examined in 61 studies using different in vitro tests against a broad spectrum of microorganisms was identified and summarized. In addition, 11 different techniques found in the literature are described in detail. An original classification of methods based on the solid and liquid matrix volatilization principle is proposed because carrier medium/matrix selection is crucial for the volatilization of any agents tested. This review should be useful for medicinal, pharmaceutical, food, and agricultural experts working in areas related to the management of infectious diseases (especially respiratory and skin infections), food preservation (active packaging), and protection of agriculture products (controlled atmosphere). It may also stimulate the interest of pharmaceutical, cosmetic, food, and agriculture industries in the research and development of new antimicrobial agents of natural origin. Since several original apparatuses previously developed for antimicrobial susceptibility testing in the vapour phase are described in this review, labware manufacturers may also be interested in this topic. The review also provides specific guidelines and recommendations for researchers studying the antimicrobial activity of volatile agents. The article will therefore appeal to communities of industrial stakeholders, pharmacists, physicians, food experts, agriculturists, and researchers in related areas such as pharmacology, medicinal chemistry, microbiology, natural product chemistry, food preservation and plant protection.
Keywords: antibacterial; broth dilution; diffusion; essential oils; plant volatiles; volatilization